Navigating the Polycrisis: Mapping the Futures of Capitalism and the Earth - Michael J. Albert (The MIT Press, 2024)
An innovative work of realism and utopianism that analyzes the possible futures of the world-system and helps us imagine how we might transition beyond capitalism.The world-system of which we are all a part faces multiple calamities: climate change and mass extinction, energy supply shocks, the economic and existential threat of AI, the chilling rise of far-right populism, and ratcheting geopolitical tensions, to name only a few. In Navigating the Polycrisis, Michael Albert seeks to illuminate how the "planetary polycrisis" will disrupt the global community in the coming decades and how we can best meet these challenges. Albert argues that we must devote more attention to the study of possible futures and adopt transdisciplinary approaches to do so. To provide a new form of critical futures analysis, he offers a theoretical framework—planetary systems thinking—that is informed by complexity theory, world-systems theory, and ecological Marxism.Navigating the Polycrisis builds on existing work on global futures and makes three main contributions. First, the book shows that in order to map out possible futures of the capitalist world-system, we must analyze the intersections and feedbacks between its numerous cascading crises—including the climate emergency, energy crises, stagflation, food system disruption, pandemics, geopolitical conflicts, and emerging technological risks. Second, the book develops an innovative transdisciplinary approach to global futures by combining critical social theory with the insights of climate and energy modelling. And third, rather than relying on idealist blueprints or ungrounded speculation, the book contributes to scholarship on postcapitalist futures by analyzing the processes, mechanisms, and struggles through which egalitarian transitions beyond capitalism might occur.A much-needed work of global futures studies, Navigating the Polycrisis brings the rigor of the natural and social sciences together with speculative imagination in order to illuminate and shape our global future.
Keywords: 300; Climate Crisis; political economy; economics; governance; environment; security; Energy; Sustainability; Climate Change; Post-Capitalism; Anthropocene